Building density derived from aerial photo mapping for physical vulnerability reduction in earthquake hazard zone of Sengon village, Central Java - Mardiatno, Djati; Susanto, Denni; Handayani, Tiara; W, Lies Rahayu; Kusumasari, Bevaola (Universitas Sebelas Maret, 2020)
Building density is an important parameter for earthquake vulnerability mapping. Sengon village, Klaten, Central Java, which located in active fault zone of Opak is still lack of strategies for risk reduction in relation to physical vulnerability, especially to building density. Â The aims of this research is to 1) calculate the building density, 2) identify the relation of building density and population number, and 3) propose vulnerability reduction planning for physical characteristic. Building density calculate from aerial photo mapping. This method is robust and effective, resulting data of building density that Dusun Belan is the densest. In Sengon village, building density and population has positive correlation. Most of buildings is inhabited by 1-2 households. Sengon village can adapt several strategies for vulnerability physical reduction, i.e. a) design a strong and eco-friendly earthquake building especially for building inhabited by>3 HH, b) provide an open space and evacuation route in denser building area.